1,2,3,4,6-Pentagalloyl Glucose, a RBD-ACE2 Binding Inhibitor to Prevent SARS-CoV-2 Infection - Chen, Rui Hong; Yang, Li Jun; Hamdoun, Sami; Chung, Sookja Kim; Lam, Christopher Wai-kei; Zhang, Kai Xi; Guo, Xiaoling; Xia, Chenglai; Law, Betty Yuen Kwan; Wong, Vincent Kam Wai (Frontiers in Pharmacology, 2021)
The outbreak of SARS-CoV-2 virus caused more than 60,074,174 confirmed cases in worldwide, which has posed a serious threat to global public health and the economy. The development of vaccines and discovery of novel drugs for COVID-19 are urgently needed. Angiotensin-converting enzyme 2 (ACE2) was reported as an entry receptor for SARS-CoV-2. And the spike-RBD of SARS-CoV-2 is responsible for binding to human ACE2 receptor (hACE2). However, there is currently no licensed effective antiviral treatment for the SARS-CoV-2 infections and the current clinical management is focused on alleviating clinical symptoms and supportive cares. In this study, we adopted molecular docking and biolayer interferometry (BLI) binding assay to determine the molecular interactions between natural small-molecule, 1,2,3,4,6-Pentagalloyl glucose (PGG) and the spike-RBD of the SARS-CoV-2. We found that PGG preferentially bound to a pocket that involved residues Glu 340 to Lys 356 of spike-RBD with a relatively low binding energy of -8 kcal/mol. BLI assay further confirmed that PGG exhibits a relatively strong binding affinity to SARS-CoV-2-RBD protein in comparison to hACE2. In addition, ELISA assay also validated that PGG could dose dependently block SARS-CoV-2-RBD binding to hACE2, whereas immunocytochemistry assay also visualized the blockage of PGG in the co-localization of spike-RBD on cell surface hACE2 in cellular level. Notably, pre-incubation of PGG with RBD-pseudotyped lentivirus also abolished the infectious property of virus in hACE2 overexpressing HEK293 cells, which mimicked the entry of wild type SARS-CoV-2 virus in human host cells. Our findings suggest that PGG may be a potential antiviral agent against the COVID-19 by blockade the fusion of SARS-CoV-2 spike-RBD to hACE2 receptors.